2020
DOI: 10.1515/almed-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Lactose tolerance test as an alternative to hydrogen breath test in the study of lactose malabsorption

Abstract: ObjectivesLactose malabsorption is generally assessed by hydrogen breath testing (HBT). However, this test is not recommended in patients with high baseline hydrogen concentrations (H2B). In addition, breath testing is not recommended in the current situation created by the COVID-19 pandemic, due to the potential infectiveness of the samples. The objective is to assess concordance between HBT and lactose tolerance test (LTT) depending on H2B concentrations.MethodsA total of 430 patients (40 years, Q1–Q3 = 28–5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In fact, a recent study carried out in Spain with 430 adults found good agreement between hydrogen breath test results and LTT results and concluded that the LTT is a good alternative when the hydrogen breath test cannot be performed (19) . Furthermore, a meta-analysis comparing the C/T-13910 polymorphism genotyping results of Northern Europeans with the hydrogen breath test and LTT results, to determine the ability of these tests to predict the genotype--phenotype relationship, showed that the LTT had higher sensitivity and specificity (94% and 90%, respectively) than the hydrogen breath test (88% and 85%, respectively) (20) .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study carried out in Spain with 430 adults found good agreement between hydrogen breath test results and LTT results and concluded that the LTT is a good alternative when the hydrogen breath test cannot be performed (19) . Furthermore, a meta-analysis comparing the C/T-13910 polymorphism genotyping results of Northern Europeans with the hydrogen breath test and LTT results, to determine the ability of these tests to predict the genotype--phenotype relationship, showed that the LTT had higher sensitivity and specificity (94% and 90%, respectively) than the hydrogen breath test (88% and 85%, respectively) (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Sendiny et al (2020) studied lactose malabsorption in patients that had not undergone bariatric treatments. They found that 26.7% of 430 patients had positive results for lactose malabsorption [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid false negative results, H 2 /CH 4 baseline levels should be low 5 , 6 and interpretation of elevated baseline levels is still uncertain 7 . We have previously shown that baseline high H 2 levels are associated with more positive lactose breath test 8 . For this reason, patient preparation is required 7 , 9 , and it includes avoiding drugs such as antibiotic or laxatives, in the previous days, or procedures that could alter colonic microbiota such as colonoscopy.…”
Section: Introductionmentioning
confidence: 93%